Mechanisms and Role of Nitric Oxide in Phytotoxicity-Mitigation of Copper - Rather, Bilal A.; Masood, Asim; Sehar, Zebus; Majid, Arif; Anjum, Naser A.; Khan, Nafees A. (Frontiers in Plant Science, 2020)
Phytotoxicity of metals significantly contributes to the major loss in agricultural productivity. Among all the metals, copper (Cu) is one of essential metals, where it exhibits toxicity only at its supra-optimal level. Elevated Cu levels affect plants developmental processes from initiation of seed germination to the senescence, photosynthetic functions, growth and productivity. The use of plant growth regulators/phytohormones and other signaling molecules is one of major approaches for reversing Cu-toxicity in plants. Nitric oxide (NO) is a versatile and bioactive gaseous signaling molecule, involved in major physiological and molecular processes in plants. NO modulates responses of plants grown under optimal conditions or to multiple stress factors including elevated Cu levels. The available literature in this context is centered mainly on the role of NO in combating Cu stress with partial discussion on underlying mechanisms. Considering the recent reports, this paper: (a) overviews Cu uptake and transport; (b) highlights the major aspects of Cu-toxicity on germination, photosynthesis, growth, phenotypic changes and nutrient-use-efficiency; (c) updates on NO as a major signaling molecule; and (d) critically appraises the Cu-significance and mechanisms underlying NO-mediated alleviation of Cu-phytotoxicity. The outcome of the discussion may provide important clues for future research on NO-mediated mitigation of Cu-phytotoxicity.